Blue Ocean Strategy Analysis At Foxtail Ktv & Lounge Jakarta In The Nightlife Tourism Industry - Michelle Lie Aulia; Yudhiet Fajar Dewantara (Pusat Publikasi Nusantara, 2025)
Competition in the night tourism industry in Jakarta, especially the PIK 2 area, is getting tougher with the presence of many similar destinations. Foxtail KTV & Lounge, one of the night tourist destinations in the region experienced a significant decrease in the number of visitors and revenue due to not having a uniqueness that can distinguish it from its competitors. This research was conducted to analyze the competition conditions faced and formulate a differentiation strategy with the Blue Ocean Strategy approach on Foxtail KTV & Lounge so that it can get out of the fierce competition and create value innovations. The conclusion from this research is that with Blue Ocean Strategy, Foxtail KTV & Lounge can formulate a strategy that can take it out of fierce competition. Therefore, Foxtail KTV & Lounge is advised to implement it immediately. Suggestions for further research, it is expected to be able to research with the execution principle of the Blue Ocean Strategy after the formulated strategy has been implemented by Foxtail KTV & Lounge.